How to Create E-Purchasing Based on Open ERP for Integrated Hospital Service System Using Quickstart Methodology - Nesya Irianis; Warih Puspitasari; Muhardi Saputra (School of Industrial and System Engineering, Telkom University, 2020)
In this research, the researcher carries out the health Industry of public hospitals in Indonesia. One of the main processes in company business processes is the purchasing of goods. One of the problems in purchasing is the absence of the system that Integrates business processes between the Inventory Department and the Purchasing Department. Hence, interfere with daily operational in RSUD XYZ like due to notification’s update delay of the goods causes unavailability stock in the warehouse, so will affect the late purchase of goods at RSUD XYZ. Odoo is a software of Enterprise Resource Planning opensource used by various types of companies. Odoo provides solutions package for Purchase Management to overcome the problem in the company. The researcher used the QuickStart Methodology to implement ERP systems. Odoo implementation with QuickStart needs through five main stages. The result of this research is the design of a planning model for Enterprise Resource Planning system of purchasing in RSUD XYZ. Moreover, Odoo makes business processes in the RSUD XYZ can be automated with real-time information, this automation and real-time data will support the RSUD XYZ to make better decision in the future.